Trade and the Internationalization of Production - Jörn Kleinert (Kiel Institute of World Economics (IfW), 2002)
Whereas many empirical studies show that the internationalization of production is driven by falling distance costs, theoretical models of the endogenous emergence of multinational enterprises predict the opposite. This paper argues that this dichotomy can be resolved if the production process is modeled more realistically by taking the use of intermediate goods into account. The argument is based on a two-country general equilibrium model set up to study companies' internationalization strategies. Companies use specific intermediate goods in their production and can choose between exports and foreign production. In choosing between these alternatives, they face a trade-off between higher variable distance costs when exporting and additional fixed costs when producing abroad. With falling distance costs, exports increase. Furthermore, the profitability of foreign production increases relative to the profitability of exports if the share of intermediate goods used is not too small. With falling distance costs, it might therefore pay for a company to become a multinational enterprise.
Keywords: F12; F23; L22; 330; Trade; Multinational Enterprise; General Equilibrium; Multinationales Unternehmen; Globalisierung; Aussenwirtschaftstheorie; Lieferanten-Kunden-Beziehung; Vorprodukt; Allgemeines Gleichgewicht; Transportkosten; Auslandsproduktion; Theorie